Developing Interactive Game-Based Learning Media to Enhance Conceptual Understanding of the Human Digestive System in Elementary Education - Mutiara, Mutiara; Safitri, Erna Retna; Raharjo, Makmum; Hamzah, Mahizer (Jurnal Pendidikan MIPA, 2025)
This study aims to develop interactive game-based learning media on the human digestive system for elementary school students and to test the validity, practicality, and potential effectiveness of the media. The development model used is the Rowntree model, which consists of three main stages: planning, development, and evaluation. This model emphasizes systematic and structured media development to ensure effective learning. Formative evaluation is conducted using the Tessmer model, which includes one-to-one and small-group trials. The media's validity was assessed by media, content, and language experts, while its practicality was tested through one-to-one and small group evaluations. Potential effectiveness of the media was measured through field testing by comparing pre-test and post-test scores. The media's validity was assessed using percentage scores of 97.7%, 87.61%, and 94.81% from media, content, and language experts, with an overall average of 93.41%, which is categorized as very valid. The practicality aspect received a score of 88.55%, indicating it is highly practical. The field test results showed an average post-test score of 85.11 and an N-Gain of 0.72, both of which are considered high. Based on these results, it can be concluded that the interactive game-based learning media has high validity, practicality, and effectiveness. This media contributes explicitly to Science and Social Studies learning through an innovative gamification approach, distinguishing it from previous studies. The use of this media not only enhances students' understanding of the human digestive system but also introduces a fun and interactive learning method, providing a new learning experience for elementary school students. The novelty of this study lies in the gamification design developed to facilitate an understanding of abstract concepts related to the human digestive system, in accordance with cognitive learning theory. This design integrates visual and audio elements to support dual coding. Additionally, this media is also designed for offline use. Keywords: development, learning media, interactive educational game, elementary school, human digestive system.